Mesh closure of epiploic foramen by ventral laparotomy in 17 horses with entrapment. (15th May 2020) - Grulke, Sigrid; Salciccia, Alexandra; Arévalo Rodríguez, José Manuel; Sandersen, Charlotte; Caudron, Isabelle; Serteyn, Didier; de la Rebière de Pouyade, Geoffroy
Abstract : Background: Epiploic foramen entrapment (EFE) of small intestine is a severe cause of strangulating small intestinal obstruction (SSI) with long‐term survival seeming lower than for other causes of SSI in horses. Different techniques via laparoscopy or laparotomy for epiploic foramen (EF) closure have been developed. Methods: This study describes a technique of peroperative mesh closure of the EF in clinical cases and their long‐term follow up. Results: In the study period of 5.5 years, 36 horses were admitted to the clinic with EFE. Of these, 17 horses had peroperative mesh closure, with resection anastomosis in 4 cases and enterotomy in 4 other cases. Fifteen of these survived to discharge. Long‐term follow‐up (one to three years, median three years) was favourable in all 15 horses not showing recurrence of EFE nor other related signs of colic. Laparoscopic evaluation of the EF was performed in two cases and showed integration of the mesh. One horse was euthanased 3.5 years after mesh placement for an unrelated cause and the mesh was well adherent obliterating the EF. Conclusion: Mesh closure of EF during emergency coeliotomy did not cause short‐term complications even in horses with resection or enterotomy and may reduce the risk of recurrence of EFE in horses.